(untitled) (Journal of Human Sciences, 2021)
This research paper deals with the study of deities and criminal funerary arc and the influence and influence of neighboring religions in it, in the time period from the beginning of the dawn of history until the end of Roman control over North Africa in the year 455 AD and the beginning of the Vandal control over it in the geographical borders of the Kingdom of Garment, which extends north to the Gulf of Sirt And towards the southeast to the Nile Valley desert and to the west and northwest, it includes Ghadames and Ghat to the areas.